Errors in dental drug prescriptions: a cross-sectional study in drugstores (Research, Society and Development, 2021)
Dental drug prescriptions aim to cure or alleviate important clinical situations such as infections, inflammation, pain, anxiety, among others. However, errors in drug prescriptions are routine, a fact that makes dispensing the drug unfeasible and impairs the treatment. The present study aimed to evaluate the knowledge of dentists to carry out prescriptions for drugs belonging to the class of antimicrobials, associated or not with other medicines. Prescriptions were analyzed from 05/10/2021 to 07/30/2021 at the time of sale and dispensing of the drugs. The pharmacological prescriptions that were in accordance with Resolution RDC No. 471 of February 23, 2021, allowed the sale and dispensing of medicines by drugstores and the prescriptions were retained and filed (1st copy of the prescription) at the pharmaceutical establishment. Incorrect prescriptions made it impossible to sell and dispense the drugs and, therefore, they were returned to the prescriber. A total of 207 dental prescriptions were analyzed, and 31.4% of the prescriptions had some error in the document. The most prevalent error was related to drug dosage, representing a total of 79.14% of all errors found in prescriptions. In addition to antimicrobials, we also find other classes of medications in drug prescriptions such as anti-inflammatories, analgesics, antifibrinolytics, antiseptics and antifungals. The present work emphasizes the importance of pharmacological knowledge and current legislation for the realization of pharmacological prescriptions that allow the sale and dispensing of medicines to the patients.